2022
DOI: 10.3390/s23010392
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Super-Resolution with Self-Calibrated Convolution for Panoramic Videos

Abstract: Panoramic videos are shot by an omnidirectional camera or a collection of cameras, and can display a view in every direction. They can provide viewers with an immersive feeling. The study of super-resolution of panoramic videos has attracted much attention, and many methods have been proposed, especially deep learning-based methods. However, due to complex architectures of all the methods, they always result in a large number of hyperparameters. To address this issue, we propose the first lightweight super-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Panoramic video is the product of a combination of multiple video technologies. Such videos allow the audience to have a wider field of view and more realistic field of view experiences ( Shang et al, 2022 ). While many studies have shown that panoramic videos are beneficial for learning, some evidence that panoramic videos are detrimental to learning has also emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Panoramic video is the product of a combination of multiple video technologies. Such videos allow the audience to have a wider field of view and more realistic field of view experiences ( Shang et al, 2022 ). While many studies have shown that panoramic videos are beneficial for learning, some evidence that panoramic videos are detrimental to learning has also emerged.…”
Section: Introductionmentioning
confidence: 99%